2014
DOI: 10.4172/2329-6836.1000137
|View full text |Cite
|
Sign up to set email alerts
|

Qualitative and Quantitative Determination of Secondary metabolites and Antioxidant Potential of Eruca sativa

Abstract: Objective: To Determine the phytochemical composition of E. sativa (stem, leaves, flowers and seeds), and evaluate their antioxidant activity. Method: Preliminary phytochemical screening for all parts of E. sativa (stem, leaves, flowers and seeds) was carried out according to standard methods. Total phenolic contents of all methanolic extracts of E. sativa, have been quantified spectrophotometrically. Hydrogen Peroxidase and 1, 1-diphenyl-2-picrylhydrazyl (DPPH) free radical assays have been used to analyze an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
19
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 25 publications
2
19
0
Order By: Relevance
“…oleifera Mill seeds [24,25,26]. Despite the limited studies on erucin, beneficial properties similar to SFN have recently been reported [27,28,29], as its ability to release H 2 S in vitro and to mediate vasodilatation [30,31]. This also led to assume that the effects showed by SFN in vivo could actually be due to its rapid interconversion to erucin [32].…”
Section: Introductionmentioning
confidence: 99%
“…oleifera Mill seeds [24,25,26]. Despite the limited studies on erucin, beneficial properties similar to SFN have recently been reported [27,28,29], as its ability to release H 2 S in vitro and to mediate vasodilatation [30,31]. This also led to assume that the effects showed by SFN in vivo could actually be due to its rapid interconversion to erucin [32].…”
Section: Introductionmentioning
confidence: 99%
“…The diseases related with the oxidative stress, such as cancer and cardiovascular problems (Andrade et al, 2005;Azmi et al, 2006) has become a serious problem in recent years. Accordingly, natural antioxidant products obtained from medicinal herbs, such as phenolic compounds, vitamins and terpenoids have been widely applied in food and medicinal fields (Cai et al, 2004;Leandro et al, 2012;Sadiq, 2014). In particular, the antioxidant activity of polyphenols, mainly flavonoids, is related with free radical-scavenging capacity, strong linkage to free ferrous ions and antimutagenic effect through high inhibition of the oxidative DNA damage (Lodovici et al, 2001;Wu et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Several biochemical constituents were evaluated qualitatively and quantitatively using standard protocols (Geetha and Geetha, 2014;Sadiq, 2014). …”
Section: Phytochemical Screening Methodsmentioning
confidence: 99%